MERUBAH MAINSHEET MINAT PERBANKAN DALAM PEMILIHAN VENDOR ATM CASH REPLENISHMENT - Gumilang, Inda (Universitas Banten Jaya, 2022)
Automatic Teller Machine (ATM) is one of the best invention of Banking technology in 20th century, it’s not only important to banking industry, for Non Banking Industry ATM is also means Business, Banking industry need many kind of Third Parties company to help them operatetheir ATM machines. One of the third party companyis ATM Cash Replenishent Service company. The number of thist hird party companies was increasing following the number of ATM machines, andtoday ATM Cash Replenishment service Industry already become tough competition business. A huge number of ATM third party makethe banking sector have high erbargaining position to choose ATM Vendor, they make a higher level of selection, manykind of “termsand condition” have tobe follow by ATM vendorsiftheywanttobeanofficial ATM thirdpartyforbanks. Everybanks has theirown standar to choose third party but they have similiarity in common, every ATM Cash Replenishment service company need theright strategy to winthe competition and keept hemstay in business. Mostly ATM Vendor service quality, corporateimage, andprice of service are theim portant factors in choosing / selecting ATM thirdparty (Vendor). This research isdesigned to describe that pattern, which one shouldbe the most important factor that influence banking industry, and itwillbe used to create a strategyfor ATM cash replenishment vendor to survive and win in the competition.